Seasonality, balance and copying mechanisms of livestock feed in Northwestern Ethiopia - Alemu Gashe Desta (Cogent Food & Agriculture)
This study aimed to determine the seasonality, feed balance, and copying mechanisms of livestock feed in the east Gojjam Zone of northwestern Ethiopia. To collect the data, the zone divided into three agroecologies (lowland, midland, and highland) and randomly selected two districts from each agroecology to represent appropriate agroecologies. The study involved 540 respondents – 45 from each peasant association – and utilized key informant interviews, focus groups, questionnaires, and direct observations for data collection. According to the findings, the study reveals that feed availability in all agroecologies fluctuates seasonally. The total dry matter and crude protein supplies per household per year in highland, midland, and lowland agroecologies were 8.69, 15.49, and 14.94 tons, and 0.05, 0.91, and 0.90 tons, respectively. The yearly dry matter and crude protein requirements for livestock in highland, midland, and lowland agroecologies were 11.9, 22.2, and 19.5 t/hh/yr, and 1.4, 2.6, and 2.5 t/hh/yr, respectively. The total amounts of dry matter and crude protein produced in the study areas satisfied only 73.3, 69.7, and 76.6%, and 32.1, 35.5, and 36.3% of the livestock requirements in the highland, midland, and lowland agroecologies, respectively. Producers in the study areas employ strategies such as purchasing feed, preserving crop residue, and reducing herd sizes to address livestock shortages of dry matter and crude protein. To address the issue, a new strategy should be employed, including managing natural pastures, increasing forage crop cultivation, providing protein-rich feed, and improving crop residue quality using effective microorganisms.